ANALISIS KEKUATAN VARIASI LONGITUDINAL BULKHEAD AREA RUANG MUAT KAPAL SPOB SALRA 115 DENGAN METODE ELEMEN HINGGA (FEM) - Arly Masneti (2022)
The strength of ship is one of the technical aspects that must be fulfill by a ship with the standards set by the Ship Classification Society. This aspect is highly affected on the safety and security of a ship when sailing, whether on rough conditions or calm sea currents. The structure of ship construction in terms of ship strength is influenced by the loading on the ship, both static and dynamic loading. The modification that will be carried out is by adding longitudinal bulkheads, so that there are 2 longitudinal bulkheads that divide the loading space into 3 tanks. The addition of this longitudinal bulkhead will certainly affect the construction strength of the SPOB Salra 115. Analysis using the finite element method, with ansys software. The output is the maximum stress and deformation at 4 loading conditions. The results of the modification of the addition of longitudinal bulkhead, the maximum stress occurrs in the loading conditions III of 9.8182 x 10^7 Pa. The maximum deformation occurs in the loading conditions II of 0.159 cm. The results showed that the stress and deformation value produced by the modification of the additional longitudinal bulkhead were smaller with a model that only used one longitudinal bulkhead. Keywords: The strength of ship, maximum stress, deformation, finite element method (FEM), Longitudinal Bulkhead